Critical velocity, anaerobic distance capacity, maximal instantaneous velocity and aerobic inertia in sprint and endurance young swimmers - Zacca, R.; Wenzel, B. M.; Piccin, J. S.; Marcilio, N. R.; Lopes, A. L.; de Souza Castro, F. A. (European Journal of Applied Physiology, 2010)
Critical velocity (CV), anaerobic distance capacity (ADC), maximal instantaneous velocity (V max), and aerobic inertia (t) were calculated from two (CV2par and ADC2par), three (CV3par, ADC3par, and V max 3par), and four-parameter model data (CV4par, ADC4par, V max 4par, and t), which were obtained from six different times and distances (50, 100, 200, 400, 800, and 1,500 m) swum in front crawl stroke under maximal intensity. Fourteen swimmers (14-15-year-old; sprint and endurance groups, each group n = 7) volunteered in this study. CV values were not influenced by the groups. The model effects showed that CV2par was higher than CV3par and CV4par regardless of the group used. In addition, CV3par and CV4par were similar. ADC seems to be better estimated using both three- and four-parameter models. V max was higher in the sprint group regardless of the model used. The models effects showed that the V max 4par was higher than the V max 3par regardless of the group. Sprint and endurance groups showed similar t values. The analysis of the models (F test, coefficient of determination R 2, and adjusted coefficient of determination R adjusted2) showed that the three-parameter model was more appropriate among the applied models. Although the four-parameter model showed better correlation for the endurance group, the inclusion of t (fourth parameter) did not significantly improve the quality of adjustment. However, it is important to emphasize the availability of another parameter for the study of bioenergetics in swimming and other sports.